2022
DOI: 10.1186/s41235-022-00371-z
|View full text |Cite
|
Sign up to set email alerts
|

Face masks versus sunglasses: limited effects of time and individual differences in the ability to judge facial identity and social traits

Abstract: Some research indicates that face masks impair identification and other judgements such as trustworthiness. However, it is unclear whether those effects have abated over time as individuals adjust to widespread use of masks, or whether performance is related to individual differences in face recognition ability. This study examined the effect of masks and sunglasses on face matching and social judgements (trustworthiness, competence, attractiveness). In Experiment 1, 135 participants across three different tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 76 publications
3
35
3
Order By: Relevance
“…Increased exposure to masked faces may also improve emotion recognition by increasing perceptual expertise. However, there is evidence for the effect of masks on other face processing tasks staying consistent over 13 months of the pandemic (Bennetts et al, 2022 ). Previous research has found that perceptual learning can shape emotion perception (Pollak et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased exposure to masked faces may also improve emotion recognition by increasing perceptual expertise. However, there is evidence for the effect of masks on other face processing tasks staying consistent over 13 months of the pandemic (Bennetts et al, 2022 ). Previous research has found that perceptual learning can shape emotion perception (Pollak et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the observations from SRs, self-reported recognition ability within the typical population showed a small but negative correlation with the magnitude of mask effects on accuracy in matched identity trials (but not other measures of performance). Interestingly, extended natural exposure of adults to faces wearing masks during the COVID-19 pandemic did not lead to an improvement in recognizing masked faces (Bennetts et al, 2022 ; Freud et al, 2021 ). In the present study, we did not investigate to what extent general face recognition ability or the amount of exposure to masks correlates with mask memory and this could be an interesting avenue for future research.…”
Section: Limitationsmentioning
confidence: 99%
“…However, at the group level, they outperformed control participants. Moreover, Bennetts et al ( 2022 ) observed that control participants had a tendency to respond more conservatively than SRs, when one of two face images wore a mask. In line with Noyes et al ( 2021 ), they also observed that both control participants’ and SRs’ matching performance decreased when one face was wearing a mask.…”
Section: Limitationsmentioning
confidence: 99%
“…In line with the observations from SRs, self-reported recognition ability within the typical population showed a small but negative correlation with the magnitude of mask effects on accuracy in matched identity trials (but not other measures of performance). Interestingly, extended natural exposure of adults to faces wearing masks during the COVID-19 pandemic did not lead to an improvement in recognizing masked faces (Bennetts et al, 2022;Freud et al, 2021). In the present study, we did not investigate to what extent general face recognition ability or the amount of exposure to masks correlates with mask memory and this could be an interesting avenue for future research.…”
Section: Limitationsmentioning
confidence: 70%